PERANCANGAN UI/UX APLIKASI PENJUALAN TIKET BUS - Kurniawan, Twojar Shahirul; Gondowastradmojo, Agus; Saputro, Indrawan Adi (Yayasan Nuraini Ibrahim Mandiri, 2025)
The design of UI/UX in a bus ticket booking application aims to enhance user experience by providing a more intuitive interface, easier navigation, and more interactive features. This study applies the User-Centered Design (UCD) method, which focuses on user needs through several stages, including user research, requirement analysis, prototyping, and user testing. Data were collected through surveys, interviews, and observations to understand user preferences and common issues faced in online bus ticket booking. The findings indicate that most users feel more comfortable with the newly developed design, particularly regarding the interactive seat selection feature and the more efficient booking process. Testing results show that 80% of users find the new design easier to use compared to previous applications, while 90% of users are satisfied with the clearer seat selection visualization. The study concludes that implementing a UCD-based design can significantly improve efficiency and user satisfaction in using bus ticket booking applications